The Motives of Dayak Kanayatn Students from Migrant Lands in Malang City Still Maintain the Malapas Tradition - Piter, Romanus -; Kencana, Julio Purba; Ranubaya, Fransesco Agnes (International Journal Ethnic, Racial and Cultural Heritage, 2025)
This study is the most recent exposition of the Malapas tradition of the Dayak Kanayatn tribe in West Kalimantan. Malapas is an act of anticipating the occurrence of Sumpanan because of not having time to eat or drink something that is desired by oneself or offered by others. The purpose of this study was to determine the motives of Dayak Kanayatn students, who are migrants in the city of Malang, East Java, who still maintain the Malapas tradition. This study uses a qualitative method to obtain a rich picture and description of the respondents. Data collection was carried out by distributing an open questionnaire in the form of a Google Forms to Dayak Kanayatn students who are studying and living in the city of Malang. The data analysis of this study used Clifford Geertz’s Thick Description theory. The results of the study show that there are six motives for students of the Dayak Kanayatn tribe, who are migrants in the city of Malang, East Java, to still maintain the Malapas tradition: (1) so as not to be a Sumpanan, (2) as a form of respecting gifts or offers of food and drink from other people, (3) as a form of respecting ancestral traditions, (4) to affirm their identity as Dayak Kanayatn people, (5) to build solidarity, (6) because it has become a habit so that it becomes a spontaneous reaction or reflex. The results of this study indicate that knowledge and awareness of local traditions among the Dayak Kanayatn tribe, who are migrants, is still very strong. This is an important capital for preserving traditions in this era of modernization.